Chickpeas and gut microbiome: Functional food implications for health - Aswani Ajay; Supriya Singh Gaur; Rafeeya Shams; Kshirod Kumar Dash; Shaikh Ayaz Mukarram; Béla Kovács (Heliyon)
Chickpea is considered a rich source of nutrients, especially protein and dietary fibre. Besides, chickpea has potential benefits for the maintenance of gut health by improving intestinal integrity and serving as a source of energy for the gut microbiota. Moreover, chickpea consumption has been found to possess anti-cancer, anti-inflammatory, and antioxidant activity. On undergoing certain treatments like soaking, dehulling, roasting, and germination, the anti-nutritional profile of chickpeas can be reduced. Observing these benefits, this review explores the impact of chickpea and its components on maintaining gut health, emphasizing various benefits. Besides, the paper comprehensively covers the nutritional composition of chickpeas and factors influencing the bioavailability of its components concerning gut health. Additionally, it outlines the mechanisms through which chickpeas influence gastrointestinal health, providing valuable insights into complex processes and potential therapeutic applications. Furthermore, the review identifies contributions that can guide future research, encouraging further exploration of chickpeas' role in gut health and the development of interventions. As a result of the presented review, chickpeas can be used as an affordable source of food, which is nutritionally stable and prevents gastrointestinal diseases.